Effect of tween-80 on stability and secretion of hydrophobic tagged-cutinases - Calado, C. R. C. (Array, 2009)
Summary: To significantly enhance the downstream processing, two cutinase variants were constructed by genetic fusion small hydrophobic peptides (WP)2 and (WP)4, respectively. However, the fusion of these peptides impairs cutinase secretion by the host cell Saccharomyces cerevisiae and increases cutinase inactivation in the culture broth due to cutinase aggregation, resulting in cutinase activities per biomass of 56 % of cutinase-(WP)2 and of 7 % of cutinase-(WP)4, in relation to cutinase without the hydrophobic tags. It was observed that the addition of non-ionic surfactant Tween-80 into the culture broth could minimise the cutinase inactivation. The addition of Tween-80 also results in the enhancement of cutinase secretion by the yeast cell, leading to 1.25 and 2.51 fold-higher extracellular cutinase-(WP)2 and cutinase-(WP)4, respectively, in relation to cultivations performed in the absence of surfactant. Therefore, the addition of Tween-80 on the culture broth partly minimises the effect of fusion of the hydrophobic tags on the inactivation of the enzymatic activity and on the reduction of the protein secretion. By this way, the use of Tween-80 on the S. cerevisiae cultivation may contribute to the efficiency enhancement of the downstream processing of tagged cutinases